(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
In present paper , we report the organic syntheses of three compounds from 4-Amino-7-chloro -2-oxo-2H –chromen -3carbaldehyde and describe the results of antibacterial activity of purified compounds.7-Chloro-4-[(2-hydroxy-benzylidene)amino]-2-oxo-2H-chromen-3-carbaldehyde(1a).4-[(2-Hydroxy-benzylidene)-amino]-7-(4-hydroxy-phenylamino)-2-oxo-2Hchromen-3-carbaldehyde (2a) ,([4-[(2-Hydroxy-benzylidene)-amino]-7-(4-hydroxyl-phenylamino)-2-oxo-chromen-3ylmethylene]-amino)-acetic acid (3a),have been synthesized and characterized using melting points , IR spectra , 1H-NMR and 13C-NMR spectra. The antibacterial activity of synthesized compounds and streptomycin and cefalexine at concentractions of 2mg/ml, 3mg/ml and 5mg/ml , have been evaluated against three strains of bacterial culture; Staphylococcus aureus, E.coli and Bacillus cereus. The compounds show bacteriostatic and bactericidal activity.